2010
DOI: 10.1603/ec09159
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological and Histopathological Effects of Boric Acid on <I>Atta sexdens rubropilosa</I> (Hymenoptera: Formicidae) Workers

Abstract: The current study compared the toxicity of different concentrations of boric acid in adult workers of Atta sexdens rubropilosa Forel (Hymenoptera: Formicidae), with toxicological bioassays, and examining the dose-dependent and time-dependent histopathological changes, of the midgut, Malpighian tubules, and postpharyngeal glands. Our results revealed the importance of conducting toxicological bioassays combined with morphological analyses of the organs of ants chronically exposed to insecticides used in commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 39 publications
(42 reference statements)
3
14
0
Order By: Relevance
“…Perhaps increased midgut size was due to vacuolization of cells. Similar ultrastructural changes were observed by Sumida et al (2010) in ants and da Silva et al (2010) in bees exposed to BA. Midgut cells were vacuolized, membranes were ruptured, and myelinated figures were observed, too.…”
Section: Discussionsupporting
confidence: 87%
“…Perhaps increased midgut size was due to vacuolization of cells. Similar ultrastructural changes were observed by Sumida et al (2010) in ants and da Silva et al (2010) in bees exposed to BA. Midgut cells were vacuolized, membranes were ruptured, and myelinated figures were observed, too.…”
Section: Discussionsupporting
confidence: 87%
“…The strongly basophilic nature of the microvilli of region III cells of the midgut (a characteristic not reported by Richardi et al () in C sancticaroli ) could be associated to the high presence of acid‐rich (DNA and RNA) organelles, such as the rough endoplasmic reticulum, the Golgi apparatus and free ribosomes, which indicate a secretory function of mitochondria in order to provide energy for active transport and the intake of substances (Jarial & Engstrom, ). Several studies in insects have shown that the midgut is a target organ for contamination, due to the absorption of xenobiotic substances acquired orally (El‐Saad, Kheirallah, & El‐Samad, ; Gutiérrez, Santos, Serrão, & Oliveira, ; Sumida et al, ). Nevertheless, there are few studies that have applied histopathological markers in the midgut of Chironomidae larvae (Lavarías et al, ; Rey, Long, Pautou, & Meyran, ; Rey, Pautou, & Meyran, ; Richardi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Boric acid has been shown to be effective against various ant species (Klotz and Moss 1996; Klotz et al 1996), and the larvae of both honeybees (da Silva Cruz et al 2010) and wax moths (Hyrsl et al 2007; Buyukguzel et al 2013). Boric acid administration has morphological effects on the midgut and malpighian tubules in leaf-cutting ants (Sumida et al 2010), leads to abnormalities in midgut cells in Argentine ants (Klotz et al 2002) and honeybee larvae (da Silva Cruz et al 2010), and promotes irregularities in both midgut tissue and the fat body in wax moths (Buyukguzel et al 2013). Nonetheless, the physiological mechanisms responsible for the mortality associated with boric acid intake are not clear.…”
mentioning
confidence: 99%